HIBRIDITAS GERAK DAN BUNYI: TRANSFORMASI METODOLOGI PENGKARYAAN TARI KONTEMPORER FLS3N BERBASIS DIGITAL AUDIO WORKSTATION - Vereki Martiano; Intania Ananada Jonisa; Susandra Jaya (Institut Seni Indonesia Surakarta, 2026)
This study aims to comprehensively analyze the methodological transformation in creating contemporary dance by utilizing Digital Audio Workstation (DAW) Studio One 6 in the FLS3N competition, focusing on the work